Inhibition of the PINK1-Parkin Pathway Enhances the Lethality of Sorafenib and Regorafenib in Hepatocellular Carcinoma - Zhang, Shun; Wang, Yixin; Cao, Yifan; Wu, Jin; Zhang, Zubin; Ren, Haigang; Xu, Xiaohui; Kaznacheyeva, Elena; Li, Qing; Wang, Guanghui (Frontiers in Pharmacology, 2022)
Hepatocellular carcinoma (HCC) is one of the most common fatal malignancies and the main cause of cancer-related deaths. The multitarget tyrosine kinase inhibitors (TKIs) sorafenib and regorafenib are systemic therapeutic drugs approved for the treatment of HCC. Here, we found that sorafenib and regorafenib injured mitochondria by inducing mitochondrial Ca2+ (mtCa2+) overload and mitochondrial permeability transition pore (mPTP) opening, resulting in mitochondria-mediated cell death, which was alleviated by cyclosporin A (CsA), an inhibitor of mPTP. Meanwhile, mPTP opening caused PINK1 accumulation on damaged mitochondria, which recruited Parkin to mitochondria to induce mitophagy. Inhibition of autophagy by the lysosomal inhibitor chloroquine (CQ) or inhibition of mitochondrial fission by mdivi-1 aggravated sorafenib- and regorafenib-induced cell death. Moreover, knockdown of PINK1 also promotes sorafenib- and regorafenib-induced cell death. An in vivo study showed that sorafenib and regorafenib inhibited HepG2 cell growth more effectively in PINK1 knockdown cells than in shNTC cells in null mice. Thus, our data demonstrate that PINK1-Parkin-mediated mitophagy alleviates sorafenib and regorafenib antitumor effects in vitro and in vivo.